2021
DOI: 10.3390/app11136211
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Endodontics as the Future Treatment of Immature Permanent Teeth

Abstract: The regenerative endodontic procedure (REP) is an alternative solution for endodontic treatment of permanent teeth with incomplete root apex development. It results in angiogenesis, reinnervation, and further root formation. Indications for REP include immature permanent teeth with necrotic pulp and inflammatory lesions of the periapical tissues. The main contraindications comprise significant destruction of the tooth tissues and a lack of patient cooperation. We distinguish the following stages of this proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 110 publications
(174 reference statements)
0
7
0
Order By: Relevance
“…The cause of post-revascularization discoloration is still debatable, but most fingers point to the presence of bismuth oxide in the conventional WMTA and its reaction with dental tissues, blood products, and irrigants used in revascularization procedures [ 16 , 17 ]. Although WMTA was developed to overcome tooth discoloration encountered with the use of the Grey mineral trioxide aggregate (GMTA), several in vitro studies had reported evidence of tooth discoloration [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of post-revascularization discoloration is still debatable, but most fingers point to the presence of bismuth oxide in the conventional WMTA and its reaction with dental tissues, blood products, and irrigants used in revascularization procedures [ 16 , 17 ]. Although WMTA was developed to overcome tooth discoloration encountered with the use of the Grey mineral trioxide aggregate (GMTA), several in vitro studies had reported evidence of tooth discoloration [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AAE guidelines recommends low concentrations of NaOCl[1.5–3%] ( 35 ). The higher concentrations of NaOCl[5.25–6%] used in seven teeth ( 23 – 26 ) and 2% chlorhexidine in one tooth ( 32 ) may be potential causes of stem cell damage ( 46 ). In the case of internal resorptions, the use of agitation may facilitate penetration of the irrigant into the resorptive defects, thus improving chemical disinfection and removal of granulation tissue, organic debris, and biofilms ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the long-term prognosis of RET still needs to be fully understood. It may be associated with complications, such as ankylosis, calcification, obliteration, tooth fracture, periapical tissue inflammation, or lack of further root growth ( 46 ). In cases of severe root resorption, revascularisation-associated intracanal calcification may help compensate for lost tooth tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The information on composition was gathered from product safety data sheets. The selected publications contain a thorough description of each group of crowns, their properties, advantages, disadvantages, indications, contraindications, preparation protocols, and treatment results ( Figure 1 ) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%